1989
DOI: 10.1007/bf02669955
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of oxirane cleavage in epoxidized soybean oil

Abstract: The kinetics of oxirane ring cleavage in epoxidized soybean oil have been studied using glacial acetic acid at 60, 70, 80 and 90~ It was shown that the reaction can be successfully modelled as first order with respect to the epoxide concentration and second order with respect to acetic acid. The reaction velocity constant at 70~ was found to be 2 • 10 -3 1-3 hrl mol-2, the frequency factor, A, = 2.321 • 107 hr I and the energy of activation, E a = 15.84 k cal mol -l. The effects of the concentration of acetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
47
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 7 publications
13
47
0
2
Order By: Relevance
“…From the results, it is confirmed that the epoxidation rate mainly depends on the formation rate of PAA which reacts with ethylenic unsaturation in the successive steps. SO 4 In the presence of AIER Iodine value Soybean oil [17] 18.3 -130 Palm Olein [6] 14.8 --Vegetable oil [16] -1 1 . 6 -Rubber seed oil [4] 15.7 -120 Karanja oil [18,19] 14.…”
Section: Activation Energy Of Epoxidation For Various Oil Systemsmentioning
confidence: 99%
“…From the results, it is confirmed that the epoxidation rate mainly depends on the formation rate of PAA which reacts with ethylenic unsaturation in the successive steps. SO 4 In the presence of AIER Iodine value Soybean oil [17] 18.3 -130 Palm Olein [6] 14.8 --Vegetable oil [16] -1 1 . 6 -Rubber seed oil [4] 15.7 -120 Karanja oil [18,19] 14.…”
Section: Activation Energy Of Epoxidation For Various Oil Systemsmentioning
confidence: 99%
“…The rate constants obtained for the reaction were in the range 0.22-69.4 × 10 −6 l.mol −1 .s −1 (Table 5), and in agreement with the values reported for MEPOL, soybean oil, cottonseed oil, mahua oil, and karanja oil. [22,23,27,32,35,36] Activation energy for the in situ epoxidation of JO obtained from the Arrhenius plot are shown in [22,23,27,33,35] …”
Section: Epoxidation Kineticsmentioning
confidence: 99%
“…The oxirane ring-opening reactions are irreversible, and so they are always favored by temperature rises. The value of E a is within the range of the activation energy found in liquid-liquid systems by Zaher et al (66.30 kJ mol 21 -using glacial AA) [9] and the calculated one by us in our study of the opening of the oxirane ring with solvated acetic acid employing sulfuric acid as homogeneous catalyst, 51.32 kJ mol 21 [12].…”
mentioning
confidence: 67%
“…Until recently, the only oxirane ring-opening reaction studies related to middle-or long-chain epoxides obtained from VO and/or FAME addressed the impact of carboxylic acids (formic, acetic or heptanoic), pure or in organic phase exclusively [8][9][10][11]. Under realistic process conditions, though, the reactants and intermediate products are solvated.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation